2023
DOI: 10.1177/08927057231190561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of teak wood on recycled HDPE/pine wood composites subjected to termite attack and accelerated weathering

Ricardo H Cruz-Estrada,
Javier Guillén-Mallette,
Edgar J López-Naranjo
et al.

Abstract: This study aimed to investigate the impact of including teak wood in recycled high-density polyethylene wood plastic composites (WPC) with pine wood on their resistance to degradation caused by termite attack and accelerated weathering. A 23 factorial experimental design was conducted with three repetitions in the center to analyze the weight loss and termite mortality during the experiments. The factors studied were the days of exposure to accelerated weathering, days of exposure to termite attack, and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…It was reported that cellulose extraction from teak wood could be utilized as a source to improve the resistivity of recycled high-density polyethylene wood plastic composite to degradation caused by termite attack and accelerating weathering. 249 This indicates that a green economy could be developed by utilizing natural fibers, which are biodegradable materials and energy-efficient, easy to manufacture, environmentally friendly, low-cost, sustainable, and biodegradable. 250,251…”
Section: Source Of Nanocellulose From Natural Fibermentioning
confidence: 99%
“…It was reported that cellulose extraction from teak wood could be utilized as a source to improve the resistivity of recycled high-density polyethylene wood plastic composite to degradation caused by termite attack and accelerating weathering. 249 This indicates that a green economy could be developed by utilizing natural fibers, which are biodegradable materials and energy-efficient, easy to manufacture, environmentally friendly, low-cost, sustainable, and biodegradable. 250,251…”
Section: Source Of Nanocellulose From Natural Fibermentioning
confidence: 99%